Association between the Angle of the Left Subclavian Artery and Procedural Time for Percutenous Coronary Intervention in Acute Coronary Syndrome Patients - Aftab Ahmed Solangi, Nasrullah, Amir Jamil, Muhammad Tahir, Jalaludin, Imran Abid (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Patients with acute coronary syndrome who receive radial access by percutaneous coronary intervention (PCI) are less likely to experience clinical adverse events. The present study aimed to associate the PCI procedural time with left subclavian artery angle in acute coronary syndrome patients. Material and Methods: This retrospective study was carried out on 124 consecutive patients who underwent percutaneous coronary intervention in Punjab Institute of Cardiology, Lahore from June 2021 to June 2022. Prior to study conduction, the ethical committee approved the study protocol. After a CT scan on admission, patients with PCI via an LRA were included in this study. The angle of left subclavian artery was measured on CT scan through coronal view as an indicator for tortuosity and was related with procedural time and clinical variables. SPSS version 26 was used for data analysis. Results: Of the total 124 consecutive patients who underwent PCI, the left radial approach was used in 60 (48.4%) acute coronary syndrome patients. The overall mean age was 64.8±12.6 years. There were 37 (29.8%) females and 87 (70.2%) males. Severe tortuosity patients (left subclavian artery angle <70 degree) had higher incidence of female gender (41.6% vs. 14.2%, p<0.001), older age (73.8±9.87 vs. 59.6±14.2 years, P<0.005), higher subclavian artery calcification (72.6% vs. 32.8%, P=0.001), and hypertension (92.6% vs. 74.8%, P<0.01) than those with angle of left subclavian artery ≥70 degrees. Total procedural time (ρ=-0.29, P=0.003), and sheath cannulation to first balloon time (ρ=-0.48, P<0.001) were negatively associated with left subclavian artery angle. Conclusion: The present study found that Left subclavian artery lower angles are indicators of tortuosity via left radial approach significantly associated with total procedural time and sheath insertion long duration to the first balloon time during percutaneous coronary intervention. Keywords: Acute coronary syndrome, Percutaneous coronary intervention, left radial access